2017
DOI: 10.1093/nar/gkx886
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for asymmetry sensing of siRNAs by the Drosophila Loqs-PD/Dcr-2 complex in RNA interference

Abstract: RNA interference defends against RNA viruses and retro-elements within an organism's genome. It is triggered by duplex siRNAs, of which one strand is selected to confer sequence-specificity to the RNA induced silencing complex (RISC). In Drosophila, Dicer-2 (Dcr-2) and the double-stranded RNA binding domain (dsRBD) protein R2D2 form the RISC loading complex (RLC) and select one strand of exogenous siRNAs according to the relative thermodynamic stability of base-pairing at either end. Through genome editing we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 78 publications
(97 reference statements)
2
26
0
Order By: Relevance
“…1c). Strong line broadening of all imino signals suggests dynamic binding involving sliding of the dsRBDs on the RNA helix, as previously shown for other dsRBDs 45,46,47 . With the shorter SRS2 stem-loop RNA, all imino signals are observable at equimolar RNA:protein ratio.…”
Section: Role Of the Length Of Dsrna For Mstau2 Tandem Domain Bindingsupporting
confidence: 77%
See 1 more Smart Citation
“…1c). Strong line broadening of all imino signals suggests dynamic binding involving sliding of the dsRBDs on the RNA helix, as previously shown for other dsRBDs 45,46,47 . With the shorter SRS2 stem-loop RNA, all imino signals are observable at equimolar RNA:protein ratio.…”
Section: Role Of the Length Of Dsrna For Mstau2 Tandem Domain Bindingsupporting
confidence: 77%
“…Sliding as initial binding mode also occurs in other RNA binding proteins such as the Drosophila protein Loqs-PD, a member of the siRNA silencing pathway. Loqs-PD contains two canonical dsRBDs that show highly dynamic binding and involves sliding along RNA stems 46 . A similar activity was also reported for the human ortholog of Loqs-PD, TAR RNA binding protein (TRBP) 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the mi/siRNA duplex termini has been proposed to be one of the determinants of strand selection and is based on the observation that the RNA strand with the less stable 5 0 end is usually selected as the guide (Khvorova et al, 2003;Schwarz et al, 2003). The heterodimers R2D2/Dcr-2 and Loqs/Dcr-2 in flies, and Dicer/TRBP in humans, are able to bind asymmetric siRNA duplexes with a well-defined orientation (Tomari et al, 2004;Noland et al, 2011;Tants et al, 2017). It has also been shown that human Dicer is dispensable for asymmetric RISC assembly (Betancur & Tomari, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Three regions of the dsRBD namely, 1) middle of helix α 1 , 2) loop between β 1 and β 2 , and 3) N-terminal residues of the helix α 2 are involved in the interactions with the backbone of the dsRNA at its minor-major-minor grove spanning a length of ~12 bp. Most dsRBDs are known to interact with dsRNAs having A-form helical structure independent of the sequence (Masliah, Barraud and Allain, 2013;Tants et al, 2017). However, the target dsRNAs often have structural defects like internal mismatches/loops and bulges perturbing the A-form helical shape of the RNA.…”
Section: Introductionmentioning
confidence: 99%